2002
DOI: 10.1046/j.1460-9568.2002.01967.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and localization of PEGylated polycyanoacrylate nanoparticles in brain and spinal cord during experimental allergic encephalomyelitis in the rat

Abstract: Under healthy conditions, the blood-brain barrier (BBB) limits the passage of solutes and cells from the blood to the CNS. During neurological diseases, BBB permeability increases dramatically and it has been hypothesized that drug carrier systems such as polymeric nanoparticles could cross the BBB and penetrate into the CNS. PEGylated polyalkylcyanoacrylate nanoparticles (long-circulating carrier) are one such system and have been investigated during experimental allergic encephalomyelitis (EAE). Brain and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 36 publications
2
86
0
1
Order By: Relevance
“…PEG-coated nanoparticles accumulate in brain tissue more effectively than non-PEG-coated nanoparticles, and those coated with high density PEG also display greater diffusion through brain parenchyma [4,16]. Of high relevance for clinical applications, PEG-coated nanoparticle accumulation is enhanced in pathological foci including gliosarcoma and Multiple Sclerosis models [17,18], possibly due to inflammation-induced BBB hyperpermeability -similar to enhanced nanoparticle permeability/retention (EPR effect) in brain tumors [19]. [20,21] exhibiting dramatically more rapid/extensive nanoparticle uptake than all other neural subtypes, in vitro [22] and in vivo [23].…”
Section: Introductionmentioning
confidence: 99%
“…PEG-coated nanoparticles accumulate in brain tissue more effectively than non-PEG-coated nanoparticles, and those coated with high density PEG also display greater diffusion through brain parenchyma [4,16]. Of high relevance for clinical applications, PEG-coated nanoparticle accumulation is enhanced in pathological foci including gliosarcoma and Multiple Sclerosis models [17,18], possibly due to inflammation-induced BBB hyperpermeability -similar to enhanced nanoparticle permeability/retention (EPR effect) in brain tumors [19]. [20,21] exhibiting dramatically more rapid/extensive nanoparticle uptake than all other neural subtypes, in vitro [22] and in vivo [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many growth factors and neuropeptides are effective when administrated into the ventricle, but lack efficiency for systemic application, explained by their failure in crossing the BBB. Now people have successfully delivered PEG-coated nanoparticles to brain and spinal cord in rat model of experimental allergic encephalomyelitis, for instance (Calvo et al 2002). It is believed that in the future more and more other brain diseases could be treated in similar manners.…”
Section: Different Routes For Brain Drug Delivery With Nanotechnologymentioning
confidence: 99%
“…For instance, in one study that used a common brain inflammation model (experimental allergic encephalomyelitis), nanoparticle delivery was pronounced in areas where the BBB had been disrupted and in regions of macrophage infiltration. 18 However, most CNS uses of nanoparticles are intended for conditions in which the BBB is intact. In the experimental allergic encephalomyelitis study just cited, the concentration of PEGylated nanoparticles was found to be increased even in brain regions in which the BBB was intact compared with non-PEGylated nanoparticles, especially in white matter.…”
Section: Issues Of Biodistributionmentioning
confidence: 99%